Multi-objective optimisation of abrasive water jet machining responses by simulated annealing and particle swarm. (1st January 2014) - Aich, Ushasta; Banerjee, Simul; Bandyopadhyay, Asish; Das, Probal Kumar
Optimum control parameter settings in complex and stochastic type processes are one of the most challenging problems to the process engineers. As such, effective model development and determination of optimal operating conditions of abrasive water jet machining process (AWJM) are reasonably difficult. In this article new modifications are proposed on two single-objective optimisation techniques, simulated annealing and particle swarm optimisation and applied to optimise two response parameters in AWJM – material removal rate (MRR) and depth of cut (DOC) simultaneously. For the optimisation purpose statistical models are developed from experimental data obtained from AWJ machining of amorphous material – borosilicate glass. Optimum results are validated and it is suggested to employ particle swarm-based proposed multi-objective optimisation technique in present case for newly modelled system due to its fast convergence and low memory space requirement.